2021
DOI: 10.1021/acs.jpcc.1c04510
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Catalytic Properties of Iron- and Nitrogen-Doped Carbon for Nitrogen Reduction through Structural Distortion: A Density Functional Theory Study

Abstract: In this study, we have performed the first-principles density functional theory calculations to predict the influence of structural distortion on the catalytic properties of Fe, N codoped carbon (Fe−N−C) for the nitrogen reduction reaction (NRR). On both FeN 4 and FeN 3 sites embedded in a graphene layer, our results show that compressive strain not only enhances the NRR activity manifested by a positive change in NRR limiting potential, but also changes the favorable NRR pathway from a hybrid path to a distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…In this research, the computational methods are very similar to those in the previous studies . All the calculations were performed with the Dmol in the Materials Studio using the DFT. The GGA (generalized gradient approximation)–PBE (Perdew–Burke–Ernzerhof method) functional was used to describe the electron exchange–correlation potential. The double numerical polarized basis set with polarization functions was used to described the wave functions of the valence electron, and a real space cutoff of 0.45 nm was used.…”
Section: Methodsmentioning
confidence: 99%
“…In this research, the computational methods are very similar to those in the previous studies . All the calculations were performed with the Dmol in the Materials Studio using the DFT. The GGA (generalized gradient approximation)–PBE (Perdew–Burke–Ernzerhof method) functional was used to describe the electron exchange–correlation potential. The double numerical polarized basis set with polarization functions was used to described the wave functions of the valence electron, and a real space cutoff of 0.45 nm was used.…”
Section: Methodsmentioning
confidence: 99%
“…The Fe active site (FeN 3 ) with higher spin moments can enhance the interaction with N atoms and push more electrons to the adsorbed N 2 molecule for its activation, showing a better catalytic eNRR performance. Besides, Shan et al reported that compressive strain could enhance the eNRR activity of FeN 4 and FeN 3 and alter the favorable reaction pathway from a hybrid to the distal path …”
Section: Computation-assisted Catalyst Design For Enrrmentioning
confidence: 99%
“…As a crustal abundant element, Fe was found to be an important component in nitrogenases for biological N 2 fixation under ambient conditions, 14,15 and much attention has been focused on its related catalysts. The FeN 4 , [16][17][18] FeC 4 13 and FeO 4 12 moieties embedded in a graphene layer have been reported to exhibit NRR activity. But, for FeC 4 -C and FeN 4 -C, the adsorption of N 2 is pretty weak with the positive adsorption energy, and the DG of the potential determining step is high over 1.0 eV.…”
Section: Introductionmentioning
confidence: 99%